Intergenerational relationship quality, sense of loneliness, and attitude toward later life among aging Chinese adults in Hong Kong - Liu, Chang; Zhou, Shuai; Bai, Xue (Frontiers in Psychology, 2022)
A positive attitude toward later life is crucial for well-being among older adults. Maintaining a healthy relationship with adult children can help reduce older parents’ sense of loneliness and nurture a positive life attitude. This study aimed to investigate the associations between multi-dimensional intergenerational relationship quality and attitudes toward later life among aging Chinese adults in Hong Kong and examine the mediating effects of sense of loneliness. Representative survey data were collected from 801 participants (aged 50 years and over) with at least one adult child. Multiple linear regression was employed to investigate the associations between overall intergenerational relationship quality with sense of loneliness as well as the attitude toward later life. To examine the mediating effects of sense of loneliness, causal mediational analyses were performed. Results demonstrated that overall intergenerational relationship quality was positively associated with aging parents’ attitude toward later life, and this relationship could be partially mediated by sense of loneliness. Among the four subdomains of intergenerational relationship quality, the influences of structural-associational solidarity and intergenerational conflict on attitude toward later life were almost fully mediated by sense of loneliness, whereas the influences of consensual-normative solidarity and affectual closeness were partially mediated. These findings contributed to an improved understanding of the relationship between intergenerational relationship quality, sense of loneliness, and attitude toward later life, and could inform future policies and service programs that promote aging adults’ social integration and positive aging.